Coaching children in sport - Stafford, Ian, 1963- (Routledge, 2011)
All coaches working with children will know that they differ substantially from adults in their capabilities, capacity for development and in their ability to meet the demands which sport places upon them. New Coaching Children in Sport provides an up-to-date, authoritative and accessible guide to core knowledge and coaching skills for anybody working with children in sport. Written by a team of leading international coaching experts, teachers, psychologists and specialists in children's issues in sport and health, the book explains why children cannot be seen as mini-adults in sport and helps.